Three-Dimensional E-Learning Application for Anatomy and Physiology of Brain - Kasinathan, Vinothini; Mustapha, Aida; Zainal Abidin, Aida Zamnah; Fajrillah, Asti Amalia Nur (International Journal of Integrated Engineering, 2018)
Neurology is one of the most challenging areas to master among the medical students owing to the complexity of the structures and their spatial arrangement. Teaching dissection and prosecutions during the anatomy lab sessions are not necessarily effective due to large class strength. To complement teaching and learning on this subject matter, a web-based, 3D interactive e-learning application called the Brainy is proposed to help medical students and lecturers to learn and teach neurology in an efficient way. Brainy merges virtual technology with learning by breaking down the brain information into three different parts, namely the lobes of brain, parts of brain, and structures of brain. Every time a student chooses to study a part of brain, the 3D model of selected part will be complemented with brief description of anatomy, physiology and applied aspects. Thus, the student will no longer need to switch different books while studying. Brainy is thus a versatile application for students to study brain in a fun and engaging way.